Mutual Benefits of Linking CDD and Nutrition Programs - Sutoto Sutoto (Indonesian Pediatric Society, 1989)
Diarrhea is one of the leading causes of illness and death in infants and children under five years of age in developing countries. An estimated 1 ,000 million diarrhea episodes occur each year in children. A recent review found an average of 3.3 episodes per year in children. Most of the diarrheal episodes occur in children in the first two years of life. The highest incidence is in the age group of 6 to 11 months, the period during which weaning foods are introduced into the child's diet. Diarrhea causes an estimated five million deaths in children under five years of age per year. About 800/o of these deaths occured in children in the first two years of life. In addition to those deaths, diarrhea is a major contributor to malnutrition.